VD_FINDINFO HC / 2021 / 5 vom 20. Januar 2021 - VD Tribunal cantonal (2021)
CONTRAT DE TRAVAIL, INDEMNITÉ DE VACANCES, DIMANCHE, JOUR FÉRIÉ, ABUS DE DROIT, DÉPENS | 2 al. 2 CC, 329a al. 1 CO, 329d al. 1 CO, 106 al. 1 CPC (CH)